The Key to Your Dreams - Trusseau, Tamara (London New Holland, 2008)
After an authoritative introduction to the different types of dreams--psychological, recurring, and predictive dreams, dreams prompted by physical and environmental conditions, and nightmares--this book offers an extensive A-to-Z dictionary of dream symbols that takes much of the mystery out of the obscure, but richly expressive language of the subconscious mind.
Include Illustrations and Index
Keywords: Dream interpretation